2006
DOI: 10.1038/sj.jid.5700020
|View full text |Cite
|
Sign up to set email alerts
|

Pseudomonas Aeruginosa- and IL-1β-Mediated Induction of Human β-Defensin-2 in Keratinocytes Is Controlled by NF-κB and AP-1

Abstract: Human beta-defensin-2 (hBD-2) is an inducible epithelial peptide antibiotic involved in cutaneous defense. Expression of hBD-2 in keratinocytes is strongly induced by IL-1beta and culture supernatants of Pseudomonas aeruginosa (PA). The use of an IL-1 receptor antagonist revealed that PA-mediated induction of hBD-2 is not dependent on IL-1. Luciferase gene reporter experiments, demonstrated that a 2,338 bp promoter fragment of hBD-2 containing three putative NF-kappaB as well as one activator protein-1 (AP-1) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
80
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(91 citation statements)
references
References 37 publications
11
80
0
Order By: Relevance
“…Here we demonstrate, for the first time to the best of our knowledge, that HBD2 expression is inducible in primary FTEC upon stimulation with poly(I:C). This is significant because HBD2 is an effective antimicrobial against bacterial (Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus) as well as viral (adenovirus, HSV, rhinovirus, and HIV) agents (68)(69)(70)(71)(72). In addition, it has chemotactic functions and can facilitate the recruitment of immune cells, such as memory T lymphocytes, iDC and mast cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…Here we demonstrate, for the first time to the best of our knowledge, that HBD2 expression is inducible in primary FTEC upon stimulation with poly(I:C). This is significant because HBD2 is an effective antimicrobial against bacterial (Escherichia coli, Pseudomonas aeruginosa, Staphylococcus aureus) as well as viral (adenovirus, HSV, rhinovirus, and HIV) agents (68)(69)(70)(71)(72). In addition, it has chemotactic functions and can facilitate the recruitment of immune cells, such as memory T lymphocytes, iDC and mast cells (39).…”
Section: Discussionmentioning
confidence: 99%
“…The cells were incubated with 10 ng/mL IL-1b and/ or the indicated concentrations of IL-12, IL-23, or IL-27 in highcalcium KBM for 48 h. The hBD-2 concentration of the culture supernatants was measured using ELISA (Peprotech, Rocky Hill, NJ). The IL-1b concentration of 10 ng/mL was adopted in this study because it did not reduce the viability of keratinocytes (>96% viable), it has been generally used in previous studies on in vitro hBD-2 production in keratinocytes [39], and this concentration was close to the IL-1b concentrations in supernatants from LPS-stimulated human macrophages [40] or tissue homogenates from the PMA-induced murine hyperplasia skin model for psoriasis [41]. Thus, IL-1b may exist at this concentration in skin wounds, infection, and inflammatory diseases.…”
Section: Hbd-2 Secretionmentioning
confidence: 99%
“…Human beta-defensins (hBD) such as hBD-2 have been shown to exert anti-HIV activity (Quiñones-Mateu et al, 2003;Sun et al, 2005;Weinberg et al, 2006). hBD is upregulated in various cell types in response to bacterial infection and pro-inflammatory cytokines (Tsutsumi-Ishii et al, 2000;Wehkamp et al, 2006). Previous studies have shown that HIV-1 virion can induce the expression of hBD, even in the absence of HIV-1 replication (Quiñones-Mateu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…NF-κB is responsible for HIV-1 Tat-induced hBD-2 expression in human B cells NF-κB signaling pathway is another pathway involved in hBD-2 (Tsutsumi-Ishii et al, 2000;Wehkamp et al, 2006). We examined HIV-1 Tat-induced NF-κB signaling cascades.…”
Section: Ap-1 Activity Is Involved In Hiv-1 Tat-induced Hbd-2 Expressmentioning
confidence: 99%
See 1 more Smart Citation